A individualização do ensino nos enriquecimentos educacionais de Renzulli e Reis: ampliando o empenho e o desempenho - Sant’Ana, Luana de André (2016)
The commitment to enhance the engagement of students and teachers in the teaching-learning process in the Brazilian educational scene has been a constant concern of educators, as well as in the achievement of higher school's scores. American researchers Joseph Renzulli and Sally Reis have been excelling in the world scenario to achieve these goals through personalized “educational enrichments”, adapted to each reality, applying the "gifted education pedagogy" through the "The Schoolwide Enrichment Model" - SEM. The present research intended to study the Model in order to identify contributions to inspire Brazilian school managers and educators. The purpose was achieved by consulting specialized literature, as well as information, articles and videos available online and through personal attendance at the event Confratute (2014, EUA). The researcher had the opportunity to collect testimonies of eight highly qualified individuals of the educational field, which were involved with the Model. The results suggest that "educational enrichments” on the basis of the "gifted education pedagogy" offered to the entire school, may benefit the Brazilian Educational System. This pedagogy aims at expanding the autonomy and creative capacity of the person, respecting and highlighting the differences and the diverse human skills. It promotes the global development of the individual and reinforces his contribution to society